2008
DOI: 10.1016/j.jog.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A Trans-Siberian Tidal Gravity Profile (TSP) for the validation of the ocean tides loading corrections

Abstract: Tidal gravity observations have been performed across Siberia, along a profile extending from Novosibirsk to the West until Sakhalin Island to the East. All the stations were occupied by the same instrument (LCR402) for periods ranging from one to more than 2 years. The first goal was to compare the observed tidal parameters of the main tidal waves O1, K1 and M2 with modelled ones computed from nine different ocean tides models: SCW80, ORI96, CSR3, FES95, FES02, CSR4, GOT00, NAO99 and TPX06. In order to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…amplitude and phase-lag factors, were compared with models of tidal deformations of the Earth. A good correlation was revealed with the DDW99 tidal model (static part) and SCW80 tidal ocean model (dynamic part) [Schiwiderski, 1983;Dehant et al, 1999;Ducarme et al, 2008]. Deviations from the global tidal tilt model amounted to 7 % for amplitudes (E-W) and +9° for phases (N-S), which can be explained by the effect of the geological structure of the Main Sayan fault.…”
Section: Strain Recordmentioning
confidence: 70%
“…amplitude and phase-lag factors, were compared with models of tidal deformations of the Earth. A good correlation was revealed with the DDW99 tidal model (static part) and SCW80 tidal ocean model (dynamic part) [Schiwiderski, 1983;Dehant et al, 1999;Ducarme et al, 2008]. Deviations from the global tidal tilt model amounted to 7 % for amplitudes (E-W) and +9° for phases (N-S), which can be explained by the effect of the geological structure of the Main Sayan fault.…”
Section: Strain Recordmentioning
confidence: 70%
“…The Trans-Siberian tidal gravity profile [16] demonstrated that modelled tidal factors, based on the mean of the 6 most recent ocean tides models (CSR4, GOT00, NAO99 with 0.5˚ × 0.5˚ grid; FES02, TPX06 wit 0.25˚ × 0.25˚ grid and FES04 with 0.125˚ × 0.125˚ grid), insure a precision of gravity tides predictions of the order of 5 nm/s 2 on the Siberian territory. The situation is more delicate at Shults Cape which is located directly on the coast.…”
Section: Timofeev Et Al 364mentioning
confidence: 92%